Anomalous flow behaviour of bauxite tailings - Nakae, T. [UNESP]; Souza, P. A. [UNESP] (My University, 1994)
This paper deals with the anomalous flow behaviour observed in two bauxite tailings pumping systems, with 450 mm and 680 mm outer diameter. In order to enlarge the pipeline lengths in the field, tests were carried out in a laboratory test-loop in order to try to understand the anomalous (intermittent) flow behaviour and to solve the problem. Based on data obtained from these laboratory tests and using a generalized REYNOLDS number it was possible to obtain results that fit the MOODY ROUSE diagram.
Keywords: Discharge (fluid mechanics); Laminar flow; Mathematical models; Ore tailings; Pipelines; Pulsatile flow; Reynolds number; Shear stress; Turbulent flow; Herschel Buckley model; Moody Rouse diagram; Pumping systems; Rheology